PENGARUH JANUARY EFFECT DAN ROGALSKI EFFECT TERHADAP ABNORMAL RETURN SAHAM DAN TRADING VOLUME ACTIVITY (Studi Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia) - Maliasari, Karina; Indrawati, Nur Khusniyah (Jurnal Ilmiah Mahasiswa FEB, 2014)
The research aims: to test the influence of January Effect and Rogalski Effect of the Abnormal Return and Trading Volume Activity in the Indonesia stock exchange.  The sample was selected by using purposive sampling technique. Methods of analysis used  the Product Moment Correlation Test, Kruskall-wallis Test, Paired Sample t-Test, and Wilcoxon Signed Rank Test.  The result showed that January Effect occurs in  the period 2012 influential against  to Abnormal return but  it  didn’t  happen,  further  more  influence on Trading Volume Activity. But Rogalski Effect didn’t exist  in  the  Indonesia  stock exchange. Keywords:January effect, Rogalski effect, abnormal  return, trading volume activity, LQ45 stock price index